New anamorphic fungi from decaying woody litter of Michelia baillonii (Magnoliaceae) in northern Thailand - Kodsueb R. (2014)
Catenosynnema micheliae gen. et sp. nov. and Oedemium micheliae sp. nov. are described from dead woody litter of Michelia baillonii (Magnoliaceae) collected from Doi Suthep-Pui National Park, Thailand. The novel anamorphic genus, Catenosynnema is characterised by synnematous conidiophores and subhyaline to pale brown, catenate conidia. The genus is similar to the anamorphic genera Seifertia and Sorocybe, both of which have catenate conidia, but differs in that its synnemata are paler in colour and of a different form. The second anamorphic taxon, Oedemium micheliae sp. nov. is distinct from other species in the genus in having conidia in short chains and possessing secondary conidiogenous ampullae. The new taxa are described, illustrated and compared with morphologically similar anamorphic fungi. © 2007 Adac.